Fine Mapping and Candidate Gene Analysis of the Gv1 Locus Controlling Green-Peel Color in Eggplant (Solanum melongena L.) - Zijian Lv; Qingmin Jin; Zhiliang Li; Tao Li; Yikui Wang; Qian You; Chao Gong; Zhou Heng; Baojuan Sun (Horticulturae, 2023)
Peel color is one of the most important appearance qualities of eggplant. The main pigment in the peel of green-fruited eggplant is chlorophyll, while white-fruited eggplant is a mutant of chlorophyll biosynthesis. A dominant gene Gv controls chlorophyll biosynthesis in eggplant peel, but none of its genes have been mapped. In this study, the white-peel inbred line 19141, the green-peel inbred line 19143, and their F2 progeny with 3:1 segregation ratio of green-peel plants to white-peel plants, were used to map the Gv1 locus by whole genome re-sequencing combined with bulked segregant analysis (BSA). The Gv1 gene was mapped in a region spanning 7.66 Mb on chromosome 8, which was narrowed down to 173.2 kb interval by screening recombinant plants with InDel and SNP markers. Sixteen candidate genes were annotated in the above closely associated region. With the aid of RNA-Seq data, it was speculated that SmAPPR2-like is the candidate gene for Gv1. The results of cloning and sequencing of SmAPPR2-like showed that there might have been three types of mutation (large deletion, frameshift variant and premature stop codon) in white-peel accessions, and of these, the deletion mutation, such as that in inbred line 19141, was the most common. Based on the sequence difference of SmAPPR2-like, molecular markers were developed to distinguish the white and green-peel accessions in natural eggplant populations, and the other types of genetic variations of SmAPPR2-like leading to white-peel accessions were elucidated. The present study not only provided reliable markers for MAS (marker-assisted selection) breeding for eggplant peel color, but also paved the way for understanding the molecular mechanism of SmAPPR2-like on chlorophyll biosynthesis in eggplant fruit.